Struktur Naratif Lakon Bratayuda Jombor - Krystiadi, Krystiadi (Institut Seni Indonesia Yogyakarta, 2022)
AbstractThe Jombor version of the Bratayuda Puppet Performance (PWLB) has developed since the end of the 19th century. Since 2005, the Jombor version of PWLB has never been performed anymore. In fact, the Jombor version of PWLB has unique pattern and structure of performance. Given these things, preservation and documentation of the Jombor version of PWLB are urgently needed. Therefore, the transcription and discovery of the Jombor version of PWLB structure pattern by Ki Kristiaji is important. This study has used Becker’s narrative structure simplified by Kasidi to find the pattern of PWLB structure. This study has also used analytical description method. The results of the analysis show that there are several scenes and war scenes of traditional patterns that are not found in the Jombor version of PWLB. These scenes include scenes of gapuran, kondur kedhaton, kapalan, pandhita, sintrèn, gambyongan, and all kinds of wars. The performance structure that is strictly followed is the division of the performance into three timelines, but the internal structure of the timeline such as the main scene is not always followed and ended by war. There is main scene followed by particular scene but is ended by war and there is main scene that is immediately ended by war. There is even one timeline in one scene followed by scene and war inside another main scene. Also, the internal structure of the main scene is not always composed by descriptions, dialogues, and actions. Some scenes of the Jombor version of PWLB do not have any descriptive elements. Meanwhile, the supporting elements in the form of sulukan (mood son), gending (instrumentalia), dhodhogan-keprakan are used by puppet masters by adjusting to the needs of the stage. Based on the results of the analysis, the arrangement of the scenes according to the traditional pattern and Becker’s narrative structure simplified by Kasidi is not rigid and coercive. These patterns are flexible according to the needs of the performanes.AbstrakPertunjukan Wayang Lakon Bratayuda (PWLB) versi Jombor tercatat telah berkembang sejak akhir abad 19. Sejak tahun 2005, PWLB versi Jombor tidak pernah dipentaskan lagi. Setelah ditelisik, PWLB versi Jombor memiliki keunikan dalam pola dan struktur lakonnya. Mengingat dua hal tersebut, usaha pelestarian dan pendokumentasian PWLB versi Jombor mendesak untuk dilakukan. Transkripsi dan penemuan pola struktur PWLB versi Jombor dengan dalang Ki Kristiaji dimaksudkan untuk menjawab hal itu. Dalam penelitian ini digunakan konsep struktur naratif Becker seperti direduksi oleh Kasidi untuk menemukan pola struktur PWLB. Adapun strategi analisis kajian ini menggunakan metode deskripsi analitik. Hasil analisis menunjukkan bahwa ada beberapa adegan dan perang menurut pola tradisi yang tidak ditemukan dalam PWLB versi Jombor. Adegan tersebut antara lain adegan gapuran, kondur kedhaton, kapalan, pandhita, sintrèn, gambyongan, dan semua jenis perang. Struktur lakon yang diikuti secara ketat adalah pembagian lakon menjadi tiga pathet, tetapi struktur internal pathet seperti jejer tidak selalu diikuti adegan dan diakhiri perang. Terdapat jejer yang diikuti adegan tetapi tidak diakhiri perang dan ada jejer yang langsung diakhiri perang. Bahkan ada satu jejer dalam suatu pathet diikuti adegan dan perang dalam kerangka pathet yang lain. Struktur internal pathet juga tidak selalu disusun oleh deskripsi, ginem, dan tindakan. Beberapa adegan PWLB versi Jombor tidak memiliki unsur deskripsi. Sedangkan unsur penyangga berupa sulukan, gending, dhodhogan-keprakan digunakan dalang dengan menyesuaikan kebutuhan pentas. Berdasarkan hasil analisis, susunan adegan menurut pola tradisi dan konsep struktur naratif Becker yang direduksi Kasidi tidak bersifat kaku dan memaksa. Pola-pola tersebut bersifat luwes disesuaikan kebutuhan lakon.